Susceptibilidad antibiótica de Escherichia coli y Klebsiella sp. Aislados de teléfonos públicos y móviles de la ciudad de Iquitos - Bardales Gonzales, Tito Reiner (2022)
The increase in bacterial resistance to antibiotics is one of the biggest current public health problems, therefore, the objective of the study was to evaluate the antibiotic susceptibility of Escherichia coli and Klebsiella sp. isolated from public and mobile phones in the city of Iquitos. 40 samples of telephones were collected (20 public and 20 mobile). Biochemical tests (Action of glucose and lactose, Voges Proskauer, Methyl Red, Tryptophan metabolism, Citrate) and antibiotic susceptibility tests (Ciprofloxacin, Trimetropim, Gentamicin, Ampicillin, Amikacin, Ceftriaxone, Tetracycline, Ceftazidine) were used. Of 20 samples analyzed from the surfaces of public telephones, 8 samples were positive for Escherichia coli and 7 samples were positive for Klebsiella sp and in the analyzes of 20 collected from mobile phones 7 samples were positive for Escherichia coli and 5 samples were positive to Klebsiella sp. Levels of resistance to Ceftriaxone, Tetracycline and Ceftazidine were found. Likewise, the Escherichia coli and Klebsiella sp. strains showed high sensitivity to Ciprofloxacin, Gentamicin, Ampicillin, with no significant differences (t = 0.288, gl = 14, P = 0.777) between both bacterial strains. Concluding that Escherichia coli presented sensitivity to a greater amount of antibiotics.